Ex-situ experimental set-up for pink guava juice fouling deposit study - Ong, C. A.; Abdul Aziz, Norashikin; Taip, Farah Saleena; Ibrahim, Mohd Nordin (Universiti Putra Malaysia Press, 2012)
A study has been conducted on pink guava juice (PGJ) fouling deposit. Several ex-situ experimental rigs were set-up to obtain PGJ fouling deposit, while the best ex-situ experimental rig was also selected. PGJ was heated at 93°C and its fouling deposit was obtained after 1 hour of heating. Then, it was used for the ex-situ cleaning study at 1 litre min-1, at several temperatures (70, 80 and 90°C), and in some chemical concentrations (1.6 v/v% of Maxiclean CP6 or 0.325 % OH–; 1.8 v/v% of Maxiclean CP6 or 0.369 % OH–; 2.0 v/v% of Maxiclean CP6 or 0.44 % OH–). The best cleaning combinations were investigated. Carbohydrate is the main content in the fouling deposit. The morphology of the deposit was studied using SEM and it showed an aggregated structure. The cleaning process improved as the temperature increased with the increasing of the chemical solution concentration. The shortest cleaning time was 40 minutes, for cleaning using 2.0 v/v % of Maxiclean CP6 (0.44 % OH–) at 90°C.